Optimalisasi kemampuan menulis mahasiswa melalui project-based learning Perkuliahan Dasar Bersama - Siti Nur Aisya Putri; Nuri Hermawan; Moulidvi Rizki Permita; Luthfita Nur Rosyidah (Nur Science Institute, 2026)
The ability to write academic papers is an important competence for university students. However, first-year students often face challenges in organizing writing structures, developing arguments, and using academic language effectively. This community service program aimed to optimize students’ academic writing skills through the Project-Based Learning (PBL) approach in the Joint Basic Course at Universitas Airlangga. The program was conducted through training, writing practice, review, revision, and presentation activities. The results showed that, out of 150 participants, 20 students, or 13.33%, were able to write reviews using concise and compact sentences; 50 students, or 33.33%, were able to construct coherent sentences; and 80 students, or 53.34%, were able to write sentences that were easy to understand. In addition, the participants successfully produced 20 academic papers with positive outcomes in the aspects of title formulation, opening sentences, explanatory sentences, transitions, and closing sentences. In conclusion, the PBL approach was effective in strengthening first-year students’ academic literacy by encouraging them to write systematically, revise their work, and communicate ideas more clearly.